The Impact of Secondary Structure on the Base-Filling of N-Methoxy-1,3-Oxazinane (MOANA) and N-Methoxy-1,3-Oxazolidine Glycol Nucleic Acid (MOGNA) Oligonucleotides - Afari (John Wiley & Sons, 2025)
Various single-stranded and hairpin-forming DNA and 2´-O-methyl-RNA oligonucleotides bearing a single (2R,3S)-4-(methoxyamino)butane-1,2,3-triol residue esterified from either O1 and O2 or O1 and O3 were synthesized. Incubation of these oligonucleotides with equimolar mixtures of formylmethyl derivatives of the canonical nucleobases and 2-methylbenzimidazole under mildly acidic conditions revealed base-filling of the modified site to be strongly favored by base stacking of a double-helix, especially an A-type one. In 2´-O-methyl-RNA hairpin oligonucleotides, base-filling of the (2R,3S)-4-(methoxyamino)butane-1,2,3-triol residue with nucleobase aldehydes followed the rules of Watson-Crick base pairing, thymine being the only exception. In single-stranded oligonucleotides or the Hoogsteen strand of triple helices, both the yield and selectivity of base-filling were much more modest.